2016
DOI: 10.1182/blood.v128.22.3231.3231
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Analyses Support Clinical Investigation of Combined Anti-CD19 CAR-T Cell, JCAR017 with Ibrutinib for the Treatment of Chronic Lymphocytic Leukemia

Abstract: Chronic lymphocytic leukemia (CLL) drives systemic immune suppression and T cell dysfunction in patients, highlighting an important consideration in this setting for the manufacturing and efficacy of adoptive cell therapies using autologous T cells. In clinical studies, anti-CD19 CAR-T cells produce durable and complete responses in leukemic and some lymphomatous B cell malignancies. While preconditioning with cyclophosphamide (Cy) and fludarabine (Flu) has improved CAR-T responses in CLL patients, reported co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Preclinical data have demonstrated that ibrutinib enhances intrinsic liso-cel activity in vitro and in vivo (110). Previous prolonged exposure of CLL patients to ibrutinib may favor tisa-cel expansion and CAR T-cell clinical activity, and in a mouse model, ibrutinib-based treatment improved CAR T-cell engraftment and cytotoxic efficacy (111).…”
Section: Cd19-directed Car T Cells and Ibrutinib For Cllmentioning
confidence: 99%
“…Preclinical data have demonstrated that ibrutinib enhances intrinsic liso-cel activity in vitro and in vivo (110). Previous prolonged exposure of CLL patients to ibrutinib may favor tisa-cel expansion and CAR T-cell clinical activity, and in a mouse model, ibrutinib-based treatment improved CAR T-cell engraftment and cytotoxic efficacy (111).…”
Section: Cd19-directed Car T Cells and Ibrutinib For Cllmentioning
confidence: 99%
“…The BTK inhibitor, ibrutinib, can modulate several immune compartments independent of its well‐known inhibitory effect on B‐cell receptor signaling . Preclinical evidence demonstrates that ibrutinib, through its modulation of T cell function, enhances the ability of CTL019 cells to expand in vivo and exert antitumor effects . In addition, T cells collected from patients exposed to ibrutinib have greater ex vivo expansion and a greater fraction of T cells with a central memory phenotype compared to T cells from CLL patients not on ibrutinib.…”
Section: Targeting Cd19 In Cllmentioning
confidence: 99%